Molecular features of copper binding proteins involved in copper homeostasis. Issue 4 (28th November 2016) - Inesi, Giuseppe
Abstract: Copper has a wide and important role in biological systems, determining conformation and activity of many metalloproteins and enzymes, such as cytochrome oxidase and superoxide dismutase . Furthermore, due to its possible reactivity with nonspecific proteins and toxic effects, elaborate systems of absorption, concentration buffering, delivery to specific protein sites and elimination, require a complex system including small carriers, chaperones and active transporters. The P‐type copper ATPases ATP7A and ATP7B provide an important system for acquisition, active transport, distribution and elimination of copper. Relevance of copper metabolism to human diseases and therapy is already known. It is quite certain that further studies will reveal detailed and useful information on biochemical mechanisms and relevance to diseases. © 2016 IUBMB Life, 69(4):211–217, 2017